Riding towards safety: examining the patterns of motorcycle accidents in Malaysia - N. Q., Radzuan; Mohd Hasnun Ariff, Hassan; Mohd Nadzeri, Omar; Nur Aqilah, Othman; Khairil Anwar, Abu Kassim (Springer, 2024)
The present study aimed to analyse the pattern of motorcycle accidents in Malaysia within five years, from 2015 to 2019. The research objective was to understand the characteristics and trends of motorcycle accidents and injuries to identify areas for improvement in motorcycle safety. Data was collected using traffic accident reports provided by the Royal Malaysian Police. The data was analysed to determine patterns and trends in the number of accidents, types of injuries, victims’ body injury location, the usage of protective headgear, and the location of opponent vehicle damage. The study results showed that motorcycle accidents remain a significant issue in Malaysia, with a relatively consistent number of accidents yearly. Head injuries were the major contributor towards motorcycle fatalities. The analysis also revealed that many fatal victims who suffered from head injuries were wearing helmets which raised doubts about the effectiveness of the protective headgear and the possibility of counterfeit helmets or improper usage. The study suggests establishing a motorcycle safety rating program similar to ASEAN NCAP for passenger cars. This program would raise awareness of motorcycle safety and aid consumers in making informed purchase decisions. Additionally, the study recommends rating the effectiveness of protective gear such as helmets in reducing head injury risk in accidents. The study provides a comprehensive analysis of motorcycle accidents in Malaysia. It highlights the need for continued efforts to improve motorcycle safety through programs and better protective headgear to decrease motorcycle accidents and injuries.